Perancangan Pembangkit Listrik Tenaga Angin dengan Turbin Angin Savonius Tipe-U untuk Kapasitas 100 W - Eka Maulana; Eddy Djatmiko; Dhidik Mahandika; Roni Cahya Putra (Jurnal Asiimetrik: Jurnal Ilmiah Rekayasa & Inovasi, 2021)
The current need for energy is many tools that use electrical energy as a source of energy from these tools, followed by the need for electrical energy in Indonesia, increasing every year. Currently, Indonesia is targeting to increase the role of new and renewable energy to maintain energy security and independence with a target of at least 23% in 2025 and 31% in 2050. The utilisation of wind energy converted into electrical energy by converting energy mechanical energy from the wind into kinetic energy in turbine blades to turn a generator that can produce electricity. This paper discusses the design of a wind power plant with a u-type Savonius turbine for a capacity of 100 W using the Pahl & Beitz method. The Savonius wind turbine designed has 3668 mm × 920 mm with galvanised steel plate material and shaft dimensions of 4310 mm × 20 mm using carbon steel material S-45 C. The average wind speed is around 4 m/s with a humidity of 30°C; if the turbine is arranged on the rotor with a suitable mechanism, it can produce a turbine rotational speed of 199.9889 rpm, a Savonius type U wind power plant designed for a capacity of 100 Watt.